2019
DOI: 10.1155/2019/9850191
|View full text |Cite
|
Sign up to set email alerts
|

Serum Irisin Predicts Posthepatectomy Complications in Patients with Hepatocellular Carcinoma

Abstract: Background. Hepatectomy remains one of the most effective treatments for patients with hepatocellular carcinoma (HCC); however, it can lead to serious complications. Irisin, a key regulator of energy metabolism, is secreted into the circulation by shedding of the extracellular portion of the fibronectin type III domain-containing 5 (FNDC5). We have shown that irisin administration alleviates liver ischemia-reperfusion injury in mice. However, the role of preoperative irisin levels in HCC patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Zhang et al measured the serum irisin levels in healthy subjects and in patients with HCC before and after hepatectomy. The serum irisin levels were significantly reduced in the cancer patients [ 94 ]. Low serum irisin levels before hepatectomy were significantly correlated with high postoperative complications (high comprehensive complication index (CCI) scores) [ 94 ].…”
Section: Role Of Irisin In Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…Zhang et al measured the serum irisin levels in healthy subjects and in patients with HCC before and after hepatectomy. The serum irisin levels were significantly reduced in the cancer patients [ 94 ]. Low serum irisin levels before hepatectomy were significantly correlated with high postoperative complications (high comprehensive complication index (CCI) scores) [ 94 ].…”
Section: Role Of Irisin In Cancermentioning
confidence: 99%
“…The serum irisin levels were significantly reduced in the cancer patients [ 94 ]. Low serum irisin levels before hepatectomy were significantly correlated with high postoperative complications (high comprehensive complication index (CCI) scores) [ 94 ]. The authors suggested a potential of irisin to be used as a serum biomarker in the diagnosis of HCC and a predictor of the complications after hepatectomy.…”
Section: Role Of Irisin In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that KIF20A is abnormally highly expressed in many tumors and is associated with a poor prognosis, including for PCa [ 16 , 17 , 19 ]. The association between FOXM1 and KIF20A in PCa was therefore investigated, with the protein levels of FOXM1 and KIF20A in DU145, VCaP, and their resistant cells being assessed.…”
Section: Resultsmentioning
confidence: 99%